The acceptance behavior of online recruitment users in Malaysia - Ibrahim O.; Ithnin N.; Muslim N.A. (2023)
In this current economic climate, many people are searching for jobs from Internet-based (online) recruitment service providers. Online recruitment has become an effective way to reach the majority of candidates globally. The purpose of this paper is to determine the pattern of acceptance behavior and to test whether the quality of website would influence users' perception. A set of working hypotheses pertaining to the relationship between quality of website and behavior were drawn from configurational acceptance behavior of online recruitment framework emphasizing a linkage between website characteristics, perceptions and behavior. This paper's conceptual model and specific hypotheses were tested using a sample of 73 respondents from the college of business administration and accounting, UNITEN. This study will benefit the recruitment service providers or other business organizations in improving their recruitment website hence the users would have positive perception towards online recruitment system.